Disputas de poder e organização pedagógica: a escola normal Nossa Senhora Auxiliadora de Anápolis/Goiás (1937-1946) - Fort, Manael Ben Elshad Jennifer St (2023)
This dissertation has the general objective of characterizing the formation of the students of the Normal Nossa Senhora Auxiliadora School- NNSAS from 1937-1946 through its contextualization within a power dispute in the city of Anápolis and the analysis of its pedagogical organization in relation to the different publics that attended specifically the normal school and the domestic school. The time frame was justified by the fact that 1937-1946 marked a period of approximately 10 years of the institution's performance since the process of transferring the Normal School of Annapolis to the sisters of the Salesian Congregation and was located within the dictatorial context of the Estado Novo and the educational dispute between pioneers and Catholics in the country. It was a bibliographical and documentary research, in which, through screening and analysis of selected documents, we were able to critically dialogue with NNSAS's sources. For the problematization of data and expansion of critical reflection on this institution and the training offered within a sociopolitical context, we relied on authors such as: Fernandes (2019); Hahner (2011); Cunha (2013); Barrozo (2016); Daros, (2013); Alves (2014); Borges (2011); Reimer D’abadia and Freitas (2022); Costa and Gonçalves (2019); Borges (2011); Ferreira (2011); Canezin and Loureiro (1994); Frago (2011); Oliveira (2020); Röhrich Ferreira and Souza Arco-Verde (2011); Silveira (2003); Foucault (1999); Ferreira Lopes (2019), among others. The results indicated that ENNSA offered at least two types of training: an elitist training for wealthy class girls and home schooling for poor girls. Her educational vision was based on Don Bosco's preventive system, in which religion served as a pretext to control and tame the students' bodies. Their imposed morality and religiosity were justified by the argument of ensuring the salvation or the transformation of girls into good Christians and honest citizens. However, he realized that this religiosity was devoid of respect and acceptance of the other, where the difference in all aspects were reasons for exclusion.